Porous hydroxyapatite microspheres, and methods of making and using the same

CN122520012BActive Publication Date: 2026-10-09WENZHOU PINZHUO BIOTECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611031780.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-09
Estimated Expiration
2046-07-13

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对现有羟基磷灰石微球对亲水性阳离子药物负载效率低的缺陷,提供一种多孔羟基磷灰石微球及其制备方法和应用

Benefits of technology

本发明对已通过静电喷雾-高温烧结制备的结晶态HA微球进行柠檬酸表面后修饰。柠檬酸通过螯合作用接枝于HA微球表面,以游离羧基(-COO-)形式存在,使微球表面由正电性转变为强负电性。这一表面电荷的逆转,使修饰后的微球能够通过静电相互作用高效吸附带正电的亲水性药物分子,载药量达到3.12%,包封率达到80.65%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122520012B_ABST
    Figure CN122520012B_ABST
Patent Text Reader

Abstract

The application belongs to the field of biomedical materials, and relates to porous hydroxyapatite microspheres as well as a preparation method and application thereof. 2 The porous hydroxyapatite microspheres are grafted with citric acid on outer surfaces and inner surfaces, have a porous structure, a specific surface area of 25-45 m 2 / g, and an average pore size of 22-35 nm. The application performs surface post-modification of crystalline HA microspheres prepared by electrostatic spraying-high temperature sintering through citric acid. The citric acid is grafted on the surface of the HA microspheres through chelation and exists in the form of free carboxyl, so that the surface of the microspheres is changed from positive electricity to strong negative electricity. The reversal of the surface charge enables the modified microspheres to efficiently adsorb positively charged hydrophilic drug molecules through electrostatic interaction, with a drug loading of 3.12% and an encapsulation efficiency of 80.65%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials and relates to a porous hydroxyapatite microsphere, its preparation method, and its application. Background Technology

[0002] Hydroxyapatite (HA) is a major inorganic component in vertebrate teeth and bones, exhibiting good biocompatibility and bioactivity. Existing technologies CN106430138A and literature (Preparation and Drug Delivery Performance Study of Strontium-Doped Hydroxyapatite Microspheres [J]. Gansu Science Journal, 2013(10):1347-1353.) record that hydroxyapatite microspheres exhibit unique advantages in the field of drug delivery due to their high specific surface area, tunable pore structure, and easy surface functionalization.

[0003] Hydroxyapatite surface with calcium ions (Ca) 2+ ) and phosphate (PO4) 3- They coexist, exhibiting an overall weakly positive or electroneutrally neutral charge. For positively charged hydrophilic drugs (such as doxorubicin hydrochloride DOX, whose molecules contain protonated amino groups -NH3), + The natural electrostatic repulsion effect results in extremely low loading efficiency for hydrophilic cationic drugs such as DOX.

[0004] Previous studies have reported the application of citric acid in the preparation of hydroxyapatite. For example, the prior art CN103058159B discloses a hollow hierarchical hydroxyapatite microsphere, its preparation method and application. The preparation method includes the following steps: (1) First, diammonium hydrogen phosphate is dissolved in deionized water, and the pH of the solution is adjusted to 5.8~6.0 with nitric acid. Then, calcium nitrate is added to make the Ca in the solution... 2+ / PO4 3- The molar ratio is 1.6~1.7. The pH of the solution is adjusted to 5.0 with nitric acid. Sodium citrate is added to the above mixture to make its concentration 9~20mg / ml. Stir continuously. (2) Then the mixture from step (1) is transferred to a high-pressure reactor. The volume of the mixture accounts for 50~80% of the total volume of the reactor. It is reacted at 80~220℃ for 1~12h, cooled naturally, washed with water 3~5 times, and dried to obtain hollow hierarchical hydroxyapatite microspheres. The prior art CN110272032A discloses a method for preparing magnesium-doped hydroxyapatite drug-loaded microspheres. Using calcium-rich shells as the main raw material, magnesium-doped hydroxyapatite microspheres are prepared by hydrothermal synthesis technology combined with sodium citrate chelating agent and loaded with anti-tumor and repair-promoting drugs. The obtained microspheres have a small spherical size (2 The microspheres are 3 μm in size and have a porous structure that ensures a large drug loading rate. They also have good biocompatibility, bone growth induction, sustained drug release and pH responsiveness. The drug-loaded microspheres can maintain drug properties and exert their effects, and can be used for drug delivery and bone defect repair. In addition, citric acid has also been used to modify hydroxyapatite nanosheets to enhance their antiviral activity (Huang Zhengqun, Tan Huirong, Zhao Xinghong, et al. Antiviral effect and mechanism of action of citric acid modified hydroxyapatite nanosheets [J]. Journal of Northeast Agricultural University, 2024, 55(8)), and as a stabilizer and chelating agent to prepare HAp@Fe3O4 nanohybrids (Role of citric acid in ultrasonically assisted hydroxyapatite@Fe3O4 functional nanohybrid formation: A detailed characterization study [J]. Journal of Science: Advanced Materials and Devices, 2025, 10(4)). However, in these existing technologies, the carboxyl group of citric acid is mainly used as a template agent, chelating agent or morphology control agent to participate in HA lattice formation or crystal growth regulation. The adsorption of cationic drugs is still mainly physical adsorption, which cannot achieve efficient loading. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing hydroxyapatite microspheres in terms of low loading efficiency for hydrophilic cationic drugs, and to provide a porous hydroxyapatite microsphere, its preparation method, and its application.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A porous hydroxyapatite microsphere has citric acid grafted onto both its outer and inner surfaces, exhibiting a porous structure; the specific surface area of ​​the porous hydroxyapatite microsphere is 25-45 m². 2 / g, with an average pore size of 22-35nm.

[0007] In this invention, citric acid is grafted onto the outer and inner surfaces of the porous hydroxyapatite microspheres, and the citric acid is expressed through carboxyl groups (-COO). -The hydroxyapatite microspheres chelate with calcium ions on the HA surface, introducing a large number of negatively charged sites and exhibiting good electrostatic adsorption for cationic hydrophilic drugs. In this invention, the inner surface refers to the walls of all channels (pores) inside the porous hydroxyapatite microspheres, i.e., the surface of the solid framework between pores. These surfaces are not directly connected to the external environment but are in contact with the fluid (such as solution or gas) within the channels. The outer surface is the outermost geometric contour surface of the porous hydroxyapatite microspheres, i.e., the outer surface of the solid sphere wall that is in direct contact with the external solution or external environment.

[0008] The suitable specific surface area of ​​the porous hydroxyapatite microspheres ensures sufficient exposure of calcium ion sites and a sufficient amount of citric acid grafting. If the specific surface area is too small, the number of carboxyl groups that can be grafted will be limited, making it impossible to establish a sufficient negative charge barrier. If the specific surface area is too large, the pore walls are prone to collapse under stress or liquid wetting after high-temperature sintering, resulting in a reduction in the actual effective adsorption sites and insufficient mechanical strength of the microspheres to maintain stability.

[0009] A suitable average pore size ensures that cationic hydrophilic drug molecules can smoothly enter the pores and not simply become trapped on the surface. If the average pore size is too small, the cationic hydrophilic drug molecules cannot enter and can only rely on extremely weak physical adsorption on the outer surface. Since the loading of cationic hydrophilic drug molecules mainly depends on hydrophobic interactions and physical confinement effects within the pores, the average pore size is too large. The drug molecules lack the binding force of the pore walls within the pores, making them prone to leakage during washing or initial release, leading to a decrease in encapsulation efficiency. Simultaneously, the release medium can enter the depths of the pores without hindrance, and the drug molecules and the carrier rely only on weak electrostatic or hydrophobic interactions, which cannot form an effective barrier. This results in a large release of the drug in a short period, failing to achieve long-term sustained release.

[0010] According to embodiments of the present invention, the present invention can be further optimized, and the optimized technical solution is as follows: In one preferred embodiment, the porous hydroxyapatite microspheres have a specific surface area of ​​26.55-40.89 m². 2 / g, with an average pore size of 23.38-30.36nm.

[0011] Based on the same inventive concept, this invention also claims protection for a method for preparing the porous hydroxyapatite microspheres, comprising the following steps: Hydroxyapatite microspheres and citric acid solution were mixed evenly and reacted with shaking at pH 5-8. The reaction product was washed and dried to obtain porous hydroxyapatite microspheres; the specific surface area of ​​the hydroxyapatite microspheres was 25-45 m². 2 / g, with an average pore size of 22-35nm.

[0012] This invention, through extensive research, has discovered that citric acid, at different pH levels, will manifest as H3Cit and H3Cit...- HCit 2- Cit 3- It exists in various forms. The one that can truly undergo effective complexation / coordination reactions with calcium ions on the HA surface is mainly H3Cit. - and Cit 3- Within the pH range of 5-8, these two forms predominate. This is the fundamental reason why the reaction can not occur. Experiments have shown that within the pH range of 5-8, citric acid can be adsorbed onto the HA surface with the opposite charge through electrostatic interaction, and can also undergo a coordination reaction with surface calcium ions through its carboxyl groups, thus realizing the complete process from adsorption to chemical grafting and forming a stable surface modification layer.

[0013] In one preferred embodiment, the oscillation reaction time is 20-40 hours.

[0014] In one preferred embodiment, the mass-to-volume ratio of hydroxyapatite microspheres to citric acid solution is (0.1-0.5) g:4 mL, preferably (0.1-0.3) g:4 mL.

[0015] Microspheres prepared under these conditions were successfully grafted with citric acid by FTIR, and subsequent drug loading was optimized.

[0016] In one preferred embodiment, the concentration of the citric acid solution is 0.3-0.5 mol / L.

[0017] Using citric acid solutions within this concentration range for post-treatment of pre-formed and sintered porous hydroxyapatite microspheres allows for full utilization of the high-concentration-driven chemical equilibrium. This enables efficient and stable chelation reactions between citric acid and exposed calcium ions on the inner walls of the pores, resulting in the in-situ grafting of numerous carboxyl groups onto the pore walls without damaging the original porous structure of the microspheres. If the citric acid concentration is too low, the driving force for the reaction between citrate ions and calcium ions on the microsphere surface is insufficient, and it is difficult to overcome the diffusion resistance within the porous structure, leading to an excessively low carboxyl group grafting density, which fails to provide effective electrostatic binding sites for cationic drugs. If the citric acid concentration is too high, excess citric acid easily forms precipitates within the pores, clogging the mesopores. Furthermore, its highly acidic environment may corrode the hydroxyapatite framework, destroying the mesoporous structure of the microspheres.

[0018] In one preferred embodiment, the method for preparing the hydroxyapatite microspheres includes the following steps: (a) Nano-hydroxyapatite and sodium alginate solution are mixed evenly to obtain a premixed solution; (b) The premixed solution was sprayed into the calcium chloride solution to prepare hydroxyapatite-calcium alginate composite microspheres; (c) The hydroxyapatite-calcium alginate composite microspheres are subjected to segmented high-temperature sintering to obtain the hydroxyapatite microspheres.

[0019] In one preferred embodiment, in step (a), the mass ratio of sodium alginate to nano-hydroxyapatite in the sodium alginate solution is (0.5-2):(1.5-6), preferably (0.5-2):6.

[0020] When the mass ratio of sodium alginate to nano-hydroxyapatite is too low, the sodium alginate content is too low, making it difficult to form a stable porous framework after high-temperature sintering. This results in insufficient mechanical strength and brittleness of the microspheres. Simultaneously, excessively large pore sizes weaken the physical confinement effect on drug molecules, leading to a decrease in encapsulation efficiency. When the mass ratio is too high, excess sodium alginate decomposes violently during sintering, causing pore collapse and closure. The microspheres become denser, resulting in a sharp decrease in specific surface area and pore volume. Furthermore, excessive aggregation of HA crystals buries a large number of calcium ion grafting sites, hindering effective citric acid modification. This invention limits the mass ratio of sodium alginate to nano-hydroxyapatite to (0.5-2):(1.5-6), achieving the highest specific surface area and optimal drug loading performance while ensuring pore structure integrity and mechanical strength.

[0021] In one preferred embodiment, the concentration of the calcium chloride solution is 3-5 wt%.

[0022] The concentration of calcium chloride solution has a significant impact on the particle size and morphology of microspheres, ensuring that the microspheres can achieve both complete solidification of droplets and stable shape maintenance during the crosslinking process.

[0023] In one preferred embodiment, the segmented high-temperature sintering process in step (c) is as follows: the temperature is increased to 90-120°C at 3-10°C / min and held for 0.5-2 hours; then the temperature is increased to 320-350°C at 3-10°C / min and held for 1-3 hours; then the temperature is increased to 580-620°C at 3-10°C / min and held for 1-3 hours; finally, the temperature is decreased to 150-250°C at 3-10°C / min and then cooled.

[0024] In one preferred embodiment, the method for preparing the hydroxyapatite microspheres includes the following steps: (1) Mix nano-hydroxyapatite with sodium alginate solution to obtain electrospray fluid; (2) Using electrostatic spraying technology, the electrospray liquid is sprayed into the calcium chloride solution under a high voltage electric field to prepare hydroxyapatite calcium alginate composite microspheres; (3) The hydroxyapatite-calcium alginate composite microspheres were sintered in segments at high temperature to obtain the hydroxyapatite microspheres.

[0025] The preparation method of this invention employs a three-step approach: electrostatic spraying, high-temperature sintering, and citric acid surface modification. Each step works synergistically to construct microspheres with a specific structure. Electrostatic spraying, by controlling the composite ratio of sodium alginate and hydroxyapatite, pre-defines the spatial distribution and density of calcium ion sites at the molecular level. The high-temperature sintering step precisely removes the calcium alginate template through segmented temperature control, fully exposing the pre-defined sites and simultaneously constructing mesoporous channels with suitable pore size and specific surface area. The citric acid modification step utilizes the unobstructed channels provided by the preceding steps to deliver the modifier into the pores, where it undergoes a chelation reaction with the exposed calcium ions, introducing negatively charged carboxyl groups in situ onto the inner wall of the pores. These three steps are sequential and indispensable. Only through their synergy can the physical retention and electrostatic adsorption of the drug be simultaneously achieved on a single microsphere platform, ultimately achieving efficient drug loading and long-lasting sustained release.

[0026] The present invention involves surface grafting after microsphere molding through post-processing. This difference in sequence directly affects the distribution of citric acid on the material surface and the functionalization effect.

[0027] In one preferred embodiment, in step (1), the mass ratio of sodium alginate to nano-hydroxyapatite in the sodium alginate solution is (0.5-2):(1.5-6), preferably (0.5-2):6.

[0028] In one preferred embodiment, in step (2), the conditions for electrostatic spraying are: voltage 16-20kV, needle inner diameter 21-34G, and feed pressure 0.5-4.5MPa.

[0029] In one preferred embodiment, the concentration of the calcium chloride solution is 3-5 wt%.

[0030] The conditions of electrostatic spraying and the concentration of calcium chloride solution have a significant impact on the particle size and morphology of microspheres, ensuring that the microspheres can achieve both complete solidification of droplets and stable shape maintenance during the crosslinking process.

[0031] In one preferred embodiment, the segmented high-temperature sintering process in step (3) is as follows: the temperature is increased to 90-120℃ at 3-10℃ / min and held for 0.5-2h; then the temperature is increased to 320-350℃ at 3-10℃ / min and held for 1-3h; then the temperature is increased to 580-620℃ at 3-10℃ / min and held for 1-3h; finally, the temperature is decreased to 150-250℃ at 3-10℃ / min and then cooled.

[0032] Based on the same inventive concept, the present invention also claims the use of the porous hydroxyapatite microspheres in the preparation of drug delivery carriers, wherein the drug comprises a cationic hydrophilic drug.

[0033] In one preferred embodiment, the cationic hydrophilic drug is one or more of doxorubicin hydrochloride, daunorubicin, epirubicin, mitoxantrone, cisplatin, carboplatin, and oxaliplatin.

[0034] Doxorubicin hydrochloride, daunorubicin, epirubicin, and mitoxantrone all belong to the same positively charged anthracycline class of drugs. They all possess protonated amino groups, which can electrostatically interact with the carboxyl groups on the surface of HA microspheres, achieving high encapsulation efficiency. Platinum-based drugs such as cisplatin, carboplatin, and oxaliplatin form positively charged hydrated ions or complex ions in aqueous solutions. These can also electrostatically interact with the carboxyl groups on the surface of HA microspheres.

[0035] In one preferred embodiment, the loading conditions for the cationic hydrophilic drug are as follows: the mass ratio of the porous hydroxyapatite microspheres to the cationic hydrophilic drug is 3-7:1, preferably 3-5:1; and the initial concentration of the cationic hydrophilic drug is 0.5-2 mg / mL, preferably 1-2 mg / mL.

[0036] In one preferred embodiment, the drug further includes a hydrophobic drug.

[0037] In one preferred embodiment, the hydrophobic drug is one or more of paclitaxel, docetaxel, and cabazitaxel.

[0038] In one preferred embodiment, the loading conditions for the hydrophobic drug are as follows: the mass ratio of the porous hydroxyapatite microspheres to the hydrophobic drug is 3-7:1, preferably 3-5:1; and the initial concentration of the hydrophobic drug is 2-5 mg / mL, preferably 2-4 mg / mL.

[0039] Compared with the prior art, the beneficial effects of the present invention are: This invention involves post-modification of crystalline HA microspheres prepared by electrostatic spraying-high-temperature sintering with citric acid. Citric acid is grafted onto the surface of the HA microspheres through chelation, thereby releasing free carboxyl groups (-COO). - The presence of a certain substance transforms the surface charge of the microspheres from positive to strong negative. This reversal of surface charge allows the modified microspheres to efficiently adsorb positively charged hydrophilic drug molecules through electrostatic interactions, achieving a drug loading of 3.12% and an encapsulation efficiency of 80.65%.

[0040] This invention achieves ultra-long-lasting sustained release of hydrophilic cationic drugs. After 46 days of in vitro release, the cumulative release rate of the drug-loaded microspheres is only 37.45%, and the release dynamics are synergistically controlled by a dual mechanism of drug diffusion and electrostatic interaction dissociation.

[0041] This invention utilizes electrostatic spraying technology to precisely control process parameters, achieving a microsphere size variation coefficient as low as 0.74%, far superior to microspheres with wide distribution prepared by traditional methods such as hydrothermal methods. Uniform particle size ensures the flowability and dispersibility of injectable formulations, avoiding problems such as syringe clogging or uneven in vivo distribution caused by uneven particle size.

[0042] This invention requires no added surfactants, organic templates, or structure-directing reagents throughout the entire process. Calcium alginate, as a natural polysaccharide self-sacrificing template, completely decomposes into CO2 and H2O during high-temperature sintering at 600℃. Compared with existing technologies, this invention avoids the biosafety risks caused by residual chemical templates. Attached Figure Description

[0043] Figure 1 This is the DSC curve of the composite microspheres.

[0044] Figure 2 The following are particle size distribution diagrams of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with four different SA:HA mass ratios: (a) is the particle size distribution diagram of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA=0.5:1.5; (b) is the particle size distribution diagram of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA=1:3; (c) is the particle size distribution diagram of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA=1.5:4.5; and (d) is the particle size distribution diagram of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA=2:6.

[0045] Figure 3 These are scanning electron microscope (SEM) images of porous hydroxyapatite microspheres; where (a) is an SEM image at a scale of 100 µm, (b) is an SEM image at a scale of 5 µm, and (c) is an SEM image at a scale of 2 µm.

[0046] Figure 4 These are the XRD patterns of SA / HA Mps, HA Mps, and CA-HA Mps.

[0047] Figure 5 These are FTIR plots of HA MPs and CA-HA MPs.

[0048] Figure 6The figures show the N2 adsorption-desorption isotherms of porous hydroxyapatite microspheres obtained by calcining composite microspheres prepared with four different SA:HA mass ratios at 600℃. Among them, (a) is the N2 adsorption-desorption isotherm of porous hydroxyapatite microspheres obtained by calcining composite microspheres prepared with SA:HA=0.5:1.5 at 600℃; (b) is the N2 adsorption-desorption isotherm of porous hydroxyapatite microspheres obtained by calcining composite microspheres prepared with SA:HA=1:3 at 600℃; (c) is the N2 adsorption-desorption isotherm of porous hydroxyapatite microspheres obtained by calcining composite microspheres prepared with SA:HA=1.5:4.5 at 600℃; and (d) is the N2 adsorption-desorption isotherm of porous hydroxyapatite microspheres obtained by calcining composite microspheres prepared with SA:HA=2:6 at 600℃.

[0049] Figure 7 The images show the pore size distribution of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with four different SA:HA mass ratios. Specifically, (a) shows the pore size distribution of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA = 0.5:1.5; (b) shows the pore size distribution of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA = 1:3; (c) shows the pore size distribution of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA = 1.5:4.5; and (d) shows the pore size distribution of porous hydroxyapatite microspheres obtained after calcination at 600℃ for composite microspheres prepared with SA:HA = 2:6.

[0050] Figure 8 The results are shown in the graphs showing the effects of microsphere specific surface area and porosity on drug loading; (a) shows the effect of microsphere specific surface area on drug loading; and (b) shows the effect of microsphere porosity on drug loading.

[0051] Figure 9 The results are shown in the graphs showing the effects of microsphere specific surface area and porosity on encapsulation efficiency; (a) shows the effect of microsphere specific surface area on encapsulation efficiency; and (b) shows the effect of microsphere porosity on encapsulation efficiency.

[0052] Figure 10 This is a bar chart showing the effect of PTX drug loading ratio on drug loading and encapsulation efficiency.

[0053] Figure 11 This is a bar chart showing the effect of DOX drug loading ratio on drug loading and encapsulation efficiency.

[0054] Figure 12 This is a bar chart showing the effect of PTX drug concentration on drug loading and encapsulation efficiency.

[0055] Figure 13This is a bar chart showing the effect of DOX drug concentration on drug loading and encapsulation efficiency.

[0056] Figure 14 This is the FTIR plot of the raw material.

[0057] Figure 15 This is the FTIR image of hydroxyapatite drug-loaded microspheres.

[0058] Figure 16 This is a high-performance liquid chromatogram of the PTX standard solution.

[0059] Figure 17 This is a high-performance liquid chromatogram of a blank microsphere solution.

[0060] Figure 18 This is a high-performance liquid chromatogram of PTX@HA Mps solution.

[0061] Figure 19 This is the standard curve of PTX solution.

[0062] Figure 20 This is the standard curve of DOX solution.

[0063] Figure 21 This is an in vitro cumulative release curve of PTX@HA Mps.

[0064] Figure 22 This is an in vitro cumulative release curve of DOX@CA-HA Mps over 0-50 days.

[0065] Figure 23 This is an in vitro cumulative release curve of DOX@CA-HA Mps over 0-25 hours.

[0066] Figure 24 The graphs show the drug loading and encapsulation efficiency of the microspheres loaded with DOX in Comparative Example 1 and Example 2; in the graphs, the data in the bar charts represent the drug loading, and the data in the line charts represent the encapsulation efficiency.

[0067] Figure 25 The figure shows the drug loading and encapsulation efficiency of the carboxylated modified microspheres loaded with DOX prepared in Comparative Example 4; in the figure, the data in the bar chart represents the drug loading and the data in the line chart represents the encapsulation efficiency. Detailed Implementation

[0068] This invention is not limited to the specific embodiments listed below. Those skilled in the art can implement this invention using various other specific embodiments based on the content disclosed herein. Any modifications or alterations made to the design structure and concept of this invention fall within the protection scope of this invention. It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.

[0069] The electrostatic spraying system used in this embodiment of the invention (referencing prior art, Loncarevic, A.; Ivankovic, M.; Rogina, A. Electrosprayed Chitosan-Copper Complex Microspheres with Uniform Size. Materials 2021, 14, 5630.) is as follows: The electrostatic spraying system mainly consists of three parts: a liquid supply system, a high-voltage DC power supply, and a microsphere collection system. First, the needle is fixed to an iron stand. The needle inlet is connected to a needle adapter via a PTFE tube, and then to a negative pressure bottle and a pressure pump. Pressure parameters are set and monitored in real time via a control panel, allowing for adjustment of the liquid inlet rate to maintain a stable sprayed liquid. In the electric field section, the negative terminal of the high-voltage power supply is connected to the needle, and the positive terminal is connected to a metal coil. Precise control of the voltage parameters allows the electrosprayed liquid to form a relatively stable Taylor cone at the needle tip, which is further stretched and broken into tiny droplets under the influence of the electric field. The collection system consists of a glass culture dish, a collection solution, and a metal coil. The culture dish containing the collection solution is placed approximately 5 cm below the needle, with the metal coil positioned directly below and in close contact with the receiving container, forming a complete electric field circuit. This allows the charged droplets to be directionally deposited into the collection solution under the guidance of the electric field, resulting in a relatively stable microsphere formation.

[0070] Example 1 Surface modification of porous hydroxyapatite microspheres (1) Preparation of electrospray fluids with different SA / HA composite ratios A mixed solution of sodium alginate and nano hydroxyapatite: Weigh appropriate amounts of sodium alginate (SA) and nano hydroxyapatite (HA), add the corresponding volume of pure water, stir at 60°C until sodium alginate (SA) is completely dissolved, and then use a homogenizer to ultrasonically disperse for 1 hour to obtain a homogeneous suspension.

[0071] (2) Preparation of receiving liquid Calcium chloride solution: Weigh an appropriate amount of anhydrous CaCl2 and add it to the corresponding volume of pure water. Stir until completely dissolved, then add a small amount of Tween 80 and stir thoroughly until well mixed.

[0072] The preparation of sodium alginate / hydroxyapatite composite microspheres (SA / HA Mps) involves five steps: preparation, collection, solidification, washing, and drying. The prepared electrospray solution is poured into a negative pressure bottle, heated and stirred at 60°C, and connected to a pressure pump using a PTFE tube. A dispensing needle is fixed to an iron stand as a single-axis nozzle. The negative terminal of a high-voltage power supply is connected to the needle, and the positive terminal is connected to a metal coil. The receiving device is grounded to provide a stable high-voltage electric field for the electrospray device. A petri dish containing CaCl2 receiving solution is placed tightly against the metal coil box and positioned 5 cm below the nozzle. The power to the control board connected to the pressure pump is turned on, and the required pressure of the electrospray solution is set to begin dispensing. When solution begins to flow from the needle tip, the high-voltage DC power supply is turned on. By adjusting the experimental voltage of the electrospray, microspheres of a specific size can be obtained in the petri dish containing the receiving solution, achieving customization of microsphere size. The collected microspheres (SA / HA Mps) were cured at room temperature for 2-4 hours and then washed with ultrapure water at least 5 times to remove residual CaCl2 from the surface of the microspheres. Finally, the microspheres were rinsed once with anhydrous ethanol, dried at 60°C, and stored at room temperature.

[0073] SA / HA Mps with a composite ratio of 0.5:1.5 were prepared under conditions of 18 kV voltage, 4% CaCl2 solution, 32G needle, and 0.6 MPa feed pressure. SA / HA Mps with a composite ratio of 1:3 were prepared under the same voltage and CaCl2 concentration conditions, using a 30G needle and a feed pressure of 0.8 MPa. SA / HA Mps with composite ratios of 1.5:4.5 and 2:6 were prepared under conditions of 18 kV voltage, 4% CaCl2 solution, 21G needle, and a feed pressure of 4.2 MPa. While ensuring sphericity and structural integrity, a series of hydroxyapatite-calcium alginate composite microspheres with uniform particle size and good dispersibility were obtained. In terms of morphological characterization, microscopic images and 3D micrographs of the SA / HA Mps showed that the prepared microspheres had a relatively uniform particle size distribution, a relatively rounded outline, and no obvious defects such as surface collapse.

[0074] The thermal properties of the composite microspheres were determined using differential scanning calorimetry (DSC) to determine a suitable sintering process. A precise amount of sample was accurately weighed and sealed individually in a standard aluminum pot. The DSC scanning temperature ranged from 25 to 400℃, with a heating rate of 10℃ / min. Results are as follows: Figure 1As shown, a significant endothermic peak appeared when the temperature reached 110.3℃. This peak mainly represents the evaporation of adsorbed water and water of crystallization within the microspheres. This is because the calcium alginate hydrogel network itself has strong hygroscopicity, retaining a significant amount of water during electrostatic spraying. The gradual removal of this water as the temperature increases corresponds to an endothermic process. At this point, the microspheres are in the drying and dehydration stage, and their physical structure has not yet undergone significant changes. Further heating to 332.8℃ revealed a sharp exothermic peak, corresponding to the thermal decomposition of the calcium alginate framework. Alginate is a natural polysaccharide; at high temperatures, its glycosidic bonds break, and the organic framework gradually carbonizes and oxidizes, releasing small molecule gases such as CO2 and H2O. This process is accompanied by significant heat release and is a crucial stage for the complete removal of the organic phase. After 332.8℃, no other significant endothermic or exothermic peaks were observed in the DSC curve, indicating that the organic components have been largely decomposed, and the remaining inorganic hydroxyapatite framework remains structurally stable even at higher temperatures. Based on the above results, in setting the sintering parameters, the temperature was first raised to 110.3℃ and held for 1 hour to facilitate the complete removal of moisture from the system. Secondly, the temperature was further raised to 332.8℃ and held for 2 hours to ensure the complete decomposition of alginate. However, at this temperature, the hydroxyapatite grains had not yet reached sufficient crystallization, and the overall framework structure remained relatively loose and prone to collapse. Therefore, after completing the first two stages, the sample was further heated to 600℃ and held for 2 hours. This further promoted the crystallization and densification of the hydroxyapatite grains, resulting in a stable crystalline phase structure. It also avoided the adverse effects of excessively high temperatures, such as excessive grain growth and over-sintering of pore walls leading to severe pore structure collapse. Furthermore, controlling the sintering temperature at 600℃ could, to some extent, inhibit the high-temperature phase transformation of hydroxyapatite, preventing the formation of excessive β-tricalcium phosphate impurities, thus ensuring that the final microspheres possess both a high specific surface area and a rich porous structure.

[0075] A certain amount of dried composite microspheres were weighed into a crucible and sintered in a box-type resistance furnace. The sintering process adopted a four-stage process: starting at 50℃, heating to 95℃ at a heating rate of 5℃ / min, holding for 1 hour, then heating to 325℃ at a heating rate of 5℃ / min, holding for 2 hours, then continuing to heat to 600℃ at a heating rate of 5℃ / min, holding for 2 hours, and finally cooling to 200℃ at a heating rate of 5℃ / min before power was cut off. After sintering, the furnace temperature was allowed to cool, and the microspheres were removed from the resistance furnace, soaked and rinsed in hydrochloric acid solution with pH=5-6, and dried to obtain porous hydroxyapatite microspheres (HA Mps), which were stored at room temperature for later use.

[0076] The particle size and particle size distribution of the porous hydroxyapatite microspheres were determined using ImageJ software. The coefficient of variation (CV) of the microspheres was calculated using the following formula: .

[0077] in It is the standard deviation of the diameter (μm). It is the average diameter (μm).

[0078] The results are as follows Figure 2 As shown, the average particle size of HA Mps with SA:HA=0.5:1.5 is 59.62±0.17μm, with a CV value of 2.85%; the average particle size of HA Mps with SA:HA=1:3 is 107.93±0.10μm, with a CV value of 0.93%; the average particle size of HA Mps with SA:HA=1.5:4.5 is 124.15±0.10μm, with a CV value of 0.81%; and the average particle size of HA Mps with SA:HA=2:6 is 257.81±0.19μm, with a CV value of 0.74%. This indicates that the microspheres have uniform particle size and a narrow particle size distribution, which can meet the requirements for customized microsphere size.

[0079] The morphology of porous hydroxyapatite microspheres was observed using scanning electron microscopy (SEM). Before observation, the microspheres were attached to a sample holder with double-sided tape and then sputtered with gold.

[0080] The results are as follows Figure 3 As shown, (a) is a scanning electron microscope (SEM) image under a 100 µm scale, (b) is a SEM image under a 5 µm scale, and (c) is a SEM image under a 2 µm scale. The microspheres exhibit good sphericity, high dispersibility, and no aggregation. The surface shows a rough morphology formed by the accumulation of nano-sized hydroxyapatite grains.

[0081] Prepare a 0.3 mol / L citric acid (CA) solution, stirring thoroughly until completely dissolved. Then, adjust the pH of the system to 5.5 using sodium hydroxide solution. Measure 4 mL of the prepared citric acid solution and add it to a sample vial pre-filled with 200 mg of porous hydroxyapatite microspheres. Place the sample at room temperature and shake for 24 h. After the reaction, wash the microspheres alternately with water and ethanol until the pH of the supernatant reaches 7. Finally, dry the washed microspheres in a 60 °C oven to obtain citric acid-modified hydroxyapatite microspheres (CA-HA Mps).

[0082] X-ray scanning was performed on hydroxyapatite-calcium alginate composite microspheres, HA Mps, and CA-HA Mps. The device was equipped with a Cu target (copper target) X-ray source with an output voltage and current of 40 kV and 40 mA, respectively, and an incident X-ray wavelength of λ = 0.154 nm. The scanning range was from 10° to 80° of 2θ, the scanning rate was 5° / min, and the step size was 0.02°.

[0083] The results are as follows Figure 4 As shown, the diffraction pattern of SA / HA Mps shows characteristic diffraction peaks of hydroxyapatite, but the peaks are broad and the intensity is low. After calcination at 600℃, the diffraction peaks of HA Mps become significantly sharper and the intensity is significantly improved, indicating that the high-temperature treatment not only effectively removes the organic template of calcium alginate, but also promotes the growth of HA grains and the improvement of crystallinity. All diffraction peaks correspond to the standard card (JCPDS No. 09-0432) of hexagonal hydroxyapatite, and the characteristic peaks are located at 2θ=25.9° (002), 31.8° (211), 32.2° (112), 32.9° (300) and 34.0° (202), etc. No other impurity peaks were detected, proving that calcination at 600℃ can obtain pure phase and well crystallized hydroxyapatite microspheres. Compared with the calcined pattern, the diffraction pattern of CA-HA Mps showed no significant changes in the position, shape, and relative intensity of the diffraction peaks, indicating that the citric acid modification process did not destroy the crystal structure of HA or introduce a new crystal phase.

[0084] The infrared spectra of SA / HA Mps, HA Mps, and CA-HA Mps were determined using Fourier transform infrared spectroscopy. Samples were prepared using the KBr pellet method, in which the sample to be tested was thoroughly mixed with KBr at a mass ratio of 1:100, ground into a fine powder, and then pelleted to obtain transparent and uniformly thick pellets. The scanning range of the infrared spectrometer was set to 400 cm⁻¹. -1 Up to 4000cm -1 .

[0085] The results are as follows Figure 5 As shown, the infrared spectrum of HA Mps is at 3573 cm⁻¹ -1 A sharp absorption peak appears at 1026 cm⁻¹, attributed to the stretching vibration of OH in the hydroxyapatite structure. -1 The nearby strong and broad peak is PO4. 3- Characteristic peak of asymmetric stretching vibration of the radical group, 602 cm⁻¹ -1 and 554cm -1 The absorption peak at that location originates from PO4. 3- The bending vibrations. These characteristic peaks indicate that the prepared microspheres have a typical hydroxyapatite structure. The infrared spectrum of CA-HA Mps shows that, after modification with citric acid, in addition to retaining the above-mentioned HA characteristic peaks, new absorption peaks also appeared. 1585cm -1 and 1420cm -1 The new peaks at these locations correspond to carboxylates (-COO) and (-COO) respectively. - The asymmetric and symmetric stretching vibrations of citric acid molecules demonstrate that citric acid molecules have been successfully grafted onto the surface of HA microspheres. Furthermore, at 1458 cm⁻¹...-1 A shoulder peak also appeared, which can be attributed to the stretching vibration of CO or the bending vibration of -CH2 in the citric acid skeleton.

[0086] The specific surface area, pore size distribution, and pore volume distribution of the samples were determined using a specific surface area and pore size analyzer. The specific surface area was calculated using the BET (Brunauer-Emmett-Teller) equation, and the pore size distribution was fitted using the BJH (Barrett-Joyner-Halenda) model. The testing conditions for the samples were as follows: the samples were first degassed at 120℃ for 8 h, followed by isothermal adsorption-desorption experiments using N2 at 77.350 K.

[0087] The corresponding nitrogen adsorption-desorption isotherms and pore size distribution curves are as follows: Figure 6 and Figure 7 As shown, according to the classification of the International Union of Pure and Applied Chemistry (IUPAC), the nitrogen adsorption-desorption isotherms of all samples belong to typical Type IV isotherms, and a relatively obvious H3-type hysteresis loop was observed in the relative pressure range of P / P0 = 0.8~1.0. This characteristic indicates that the microspheres are mainly composed of nanoscale hydroxyapatite grains, which overlap to form a large number of slit-like mesoporous structures. These mesopores and slit-like channels generated by the accumulation of nanocrystals provide the necessary physical space and channels for drug molecule entry, loading, and subsequent diffusion and migration, and also provide a structural basis for the optimization of subsequent drug loading performance and release behavior.

[0088] Specific surface area, pore volume, average pore diameter, and porosity are summarized in Table 1.

[0089]

[0090] With the gradual increase of the total solids content of SA:HA, the BET specific surface area and pore volume of the microspheres first increased slightly and then decreased significantly. When SA:HA = 0.5:1.5, the specific surface area was 39.46 m². 2 / g, pore volume is 0.287cm³ 3 / g, with an average pore size of 29.07nm; when the ratio is increased to 1:3, the specific surface area increases to a maximum of 40.89m². 2 / g, pore volume decreased slightly to 0.239cm 3 / g, the average pore size decreased to 23.38nm. This indicates that at this ratio, a moderate sodium alginate content is beneficial for forming a finer and more numerous mesoporous network, enabling the microspheres to achieve the highest relative specific surface area. When the SA:HA ratio was further increased to 1.5:4.5, the specific surface area and pore volume decreased to 26.55m³. 2 / g and 0.200cm 3The average pore size increased to 30.17 nm / g. This trend may be related to the high sodium alginate content, which leads to more intense decomposition of the organic phase during sintering. This can cause some of the originally smaller pores to merge or partially collapse, resulting in a pore structure with larger pore sizes but a lower total surface area. When the ratio continues to increase to 2:6, the specific surface area drops significantly to only 3.80 nm. 2 / g, and the pore volume also decreased to 0.029cm. 3 The average pore size was 30.36 nm, and the porosity was only 8.4%. This indicates that the porous characteristics of the microspheres had been significantly weakened at this point. This result is likely due to the high SA content, which increased the viscosity of the precursor solution and significantly hindered gas escape during the sintering stage. As a result, the internal structure of the microspheres gradually became denser, and after sintering, the hydroxyapatite grains agglomerated severely, most of the original mesopores disappeared, leaving only a small number of larger pore structures.

[0091] Example 2 Preparation and process optimization of drug-loaded microspheres A certain mass of PTX was weighed and dissolved in dichloromethane to prepare a PTX solution, while DOX was dissolved in PBS to prepare a DOX solution. The corresponding mass of microspheres was weighed and placed in brown sample vials, and 1 mL of the above drug solution was added to each vial, with three replicates prepared for each group. Each sample vial was placed in a 37℃ constant temperature shaking incubator for 24 hours in the dark for adsorption. After shaking, the samples were removed, centrifuged, and the supernatant was collected. The precipitate was dried in a 37℃ vacuum drying oven to obtain the corresponding drug-loaded microspheres. A single-factor analysis was used, with drug loading (DL%) and encapsulation efficiency (EE%) as indicators, to investigate the effects of microsphere pore size, drug-to-microsphere ratio (drug to microsphere mass ratio), and drug concentration. All other process parameters were kept constant while studying the effect of each parameter. The condition with the highest DL% and EE% was finally selected as the basis for the drug loading process in subsequent in vitro release experiments.

[0092] Determination of drug loading and encapsulation efficiency of drug-loaded microspheres Accurately weigh 5 mg of drug-loaded microspheres, place them in a centrifuge tube, and crush them. Add 6 mL of methanol to the PTX-loaded microspheres and 6 mL of HCl solution (pH=3) to the DOX-loaded microspheres. Sonicate the centrifuge tubes for 30 min, then centrifuge at 4000 rpm for 10 min. Collect the supernatant and filter it through a 0.22 μm filter membrane. Analyze the supernatant from the PTX-loaded microspheres under the above chromatographic conditions, and calculate the PTX content in the sample based on the PTX standard curve. For the DOX-loaded microspheres, measure the fluorescence intensity of the supernatant using a fluorescence spectrometer, and calculate the DOX content loaded in the microspheres based on the DOX standard curve. Calculate the drug loading (DL%) and encapsulation efficiency (EE%) of the microspheres using the following formulas.

[0093] ; .

[0094] Where W1 and W2 represent the weight of the drug in the microsphere and the weight of the entire microsphere, respectively, and W3 represents the weight of the drug in the rinsing solution. All results are expressed as mean ± standard deviation (n=3).

[0095] The effect of microsphere pore size on drug loading performance was investigated. Under the condition of fixed PTX and DOX drug concentrations of 1 mg / mL and drug loading ratio of 1:5, the effects of HA Mps adsorbing PTX with different composite ratios SA:HA=0.5:1.5, 1:3, 1.5:4.5, and 2:6 and CA-HA Mps adsorbing DOX with different composite ratios SA:HA=0.5:1.5, 1:3, 1.5:4.5, and 2:6 on DL% and EE% were investigated.

[0096] The results are as follows Figure 8 and Figure 9 As shown. Among them, Figure 8 (a) shows the effect of microsphere specific surface area on drug loading; (b) shows the effect of microsphere porosity on drug loading. Figure 9 Figure (a) shows the effect of microsphere specific surface area on encapsulation efficiency; Figure (b) shows the effect of microsphere porosity on encapsulation efficiency. The results show that with changes in the mass ratio of sodium alginate to hydroxyapatite, both the drug loading percentage (DL%) and EE% exhibit a trend of first increasing and then decreasing. Compared to other composite ratios, microspheres with an SA:HA ratio of 1:3 have the largest specific surface area and the smallest pore size, providing abundant adsorption sites for drug molecules. When the SA:HA ratio is lower than 1:3 (e.g., 0.5:1.5), although the pore volume is relatively large, the specific surface area decreases slightly, and the average pore size is larger. Excessively large pore sizes significantly weaken the physical constraint on PTX and DOX molecules, making it easier for drug molecules to diffuse out of the pores, leading to increased drug loss during subsequent washing or separation processes, and thus a decrease in encapsulation efficiency. When the SA:HA ratio is higher than 1:3 (e.g., 1.5:4.5 and 2:6), although the absolute content of sodium alginate increases, the excessive decomposition of organic matter during high-temperature sintering leads to thinning of the pore walls, collapse of some pores, and even the formation of excessively large macropores, resulting in a significant decrease in specific surface area and porosity. This not only weakens the physical retention capacity of the microspheres for drug molecules but also reduces the accessibility of surface modification (i.e., citric acid molecules have difficulty entering collapsed or blocked pores) and the grafting density of carboxyl groups, thus causing a significant decrease in both drug loading and encapsulation efficiency of the two types of drug-loaded microspheres.

[0097] To investigate the effect of drug loading ratio on drug loading performance, with the concentrations of PTX and DOX fixed at 1 mg / mL, the adsorption conditions of HA Mps with SA:HA=1:3 and CA-HA Mps with SA:HA=1:3 for DOX adsorption were selected. The effects of two different drug loading ratios of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, and 2:1 on DL% and EE% were investigated.

[0098] The results are as follows Figure 10 and Figure 11 As shown, both drug loading and encapsulation efficiency initially increased and then decreased with the change in drug-to-carrier ratio, reaching their highest values ​​(DL% and EE%) at a ratio of 1:5. When the drug-to-carrier ratio was low (2:1-1:4), the amount of drug relative to the carrier was relatively large, resulting in a sufficient number of drug molecules contacting the microspheres per unit mass, thus maintaining a high drug loading level. However, the carrier surface has limited adsorption sites. In cases of drug excess, these sites are quickly filled, leaving a large number of drug molecules unbound by the microspheres and remaining in the solution, leading to a significantly low encapsulation efficiency. Only when the drug-to-carrier ratio is moderate (1:3-1:5) can drug molecules have sufficient opportunity to enter the pores and interact fully with the binding sites without excessive surface adsorption or drug waste due to carrier excess. Therefore, both drug loading and encapsulation efficiency are optimal.

[0099] The effect of drug concentration on drug loading performance was investigated. With a fixed drug-to-load ratio of 1:5, HA Mps with SA:HA=1:3 adsorbed PTX and CA-HA Mps with SA:HA=1:3 adsorbed DOX were selected. The effects of different drug concentrations of 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL and 5 mg / mL on DL% and EE% were investigated.

[0100] The results are as follows Figure 12 and Figure 13 As shown, with increasing concentrations of PTX and DOX, the adsorption capacity of both drugs gradually increased, while the encapsulation efficiency first increased and then decreased. However, the peak concentrations for the two drugs differed significantly: the optimal concentration for PTX was 4 mg / mL, while for DOX it was 1 mg / mL. For PTX, when the concentration reached 4 mg / mL, the hydrophobic binding sites tended to saturate, at which point the drug loading reached its peak. However, when the concentration continued to increase to 5 mg / mL, excess PTX molecules might aggregate in the solution or form a loosely adsorbed multilayer on the microsphere surface. In this multilayer adsorption, the binding force between the outer layer of drug and the microsphere surface is weak, making it easy to detach during subsequent washing, leading to a decrease in encapsulation efficiency.

[0101] For DOX, due to its high affinity for electrostatic interactions, DOX can rapidly occupy the limited carboxyl binding sites on the microsphere surface even at low concentrations. As the concentration increases from low to high, the drug loading and encapsulation efficiency rise rapidly, reaching adsorption saturation at 1 mg / mL, where both are at their maximum values. When the concentration exceeds 1 mg / mL, the carboxyl sites on the microsphere surface are completely occupied, and excess DOX molecules cannot be effectively adsorbed, remaining in the solution and leading to a significant decrease in encapsulation efficiency.

[0102] In summary, the optimal drug loading conditions for PTX@HA Mps are: SA:HA = 1:3 HA Mps, drug loading ratio of 1:5, PTX concentration of 4 mg / mL, and adsorption at 37℃ with shaking for 24 h. Under these conditions, the drug loading is 3.14 ± 0.14%, and the encapsulation efficiency is 50.74 ± 4.73%.

[0103] The optimal drug loading conditions for DOX@CA-HA Mps were: SA:HA = 1:3 CA-HA Mps, drug loading ratio 1:5, DOX concentration 1 mg / mL, and adsorption with shaking at 37℃ for 24 h. Under these conditions, the drug loading was 3.12 ± 0.28%, and the encapsulation efficiency was 80.65 ± 3.47% (subsequent experiments were conducted using this drug loading process).

[0104] Infrared spectra of HA Mps, PTX, PTX@HA Mps, CA-HA Mps, DOX, and DOX@CA-HA Mps were determined using an infrared spectrometer. Samples were prepared using the KBr pellet method, where the sample and KBr were thoroughly mixed at a mass ratio of 1:100, ground into a fine powder, and then pelleted to obtain transparent and uniformly thick pellets. The scanning range of the infrared spectrometer was set to 400 cm⁻¹. -1 Up to 4000cm -1 .

[0105] Raw material charts Figure 14 As shown, in the DOX atlas, 3330cm -1 (OH / NH stretching vibration), 1580cm -1 (NH bending vibration and C=O stretching vibration) and 1285cm -1 A characteristic peak appears at (COC stretching vibration); at 1730 cm⁻¹ in the PTX spectrum. -1 (C=O stretching vibration of ester carbonyl group), 1645 cm⁻¹ -1 (Amide I band) and 1245cm -1 A characteristic absorption peak appears at the (CO stretching vibration) point.

[0106] Infrared spectra of the two drug-loaded microspheres are as follows Figure 15As shown, the infrared spectrum of DOX@CA-HA Mps at 1580 cm⁻¹ -1 The characteristic absorption peak of DOX appeared nearby, which was slightly broadened and redshifted slightly compared to pure DOX. This is attributed to the protonated amino groups (-NH3) in the DOX molecule. + ) and CA-HA Mps surface carboxyl groups (-COO) - Electrostatic interactions between ) and hydrogen bonding between hydroxyl groups. Simultaneously, 3570cm -1 The enhancement of the nearby broad peak further confirms the presence of hydrogen bonding. For PTX@HA Mps, its spectrum retains the characteristic peaks of the HA framework while exhibiting enhancement at 1730 cm⁻¹. -1 and 1245cm -1 The characteristic absorption peaks of PTX are clearly visible, and these peak positions are not significantly shifted compared to pure PTX, indicating that PTX is mainly loaded into the pores of HA microspheres through physical adsorption and hydrophobic interactions, and does not form strong chemical bonds with the support framework.

[0107] Example 3 Establishment of a method for determining PTX and DOX content in microspheres The high-performance liquid chromatography (HPLC) conditions are as follows: Column: Kromasil 100-5-C18 (5μm, 4.6×250mm); Mobile phase: Acetonitrile-water (57:43, v / v); Flow rate: 1.0 mL / min; Detection wavelength: 229nm; Column temperature: 25℃±5℃; Sample size: 10 μL.

[0108] Specificity determination Accurately weigh a certain amount of PTX, dissolve it in methanol, and prepare a standard solution with a concentration of 50 μg / mL. Simultaneously, weigh a certain amount of blank microspheres and drug-loaded microspheres, add the corresponding volume of methanol, thoroughly crush the microspheres, and sonicate them. After sonication, all samples were filtered through a 0.22 μm organic filter membrane and then analyzed under the chromatographic conditions described above. The corresponding chromatograms were then exported. By comparing the chromatographic peaks of the standard solution, blank microsphere solution, and drug-loaded microsphere solution, it was determined whether other excipients and solvents would interfere with the detection of PTX.

[0109] The high-performance liquid chromatograms of PTX standard solution, blank microspheres, and PTX@HA Mps are shown below. Figure 16 , Figure 17 , Figure 18As shown in the chromatogram, PTX eluted around 6.2 min without interference from excipients or solvents, indicating that the chromatographic conditions provided for detecting PTX in drug-loaded sustained-release microspheres are highly specific.

[0110] Determination of standard curve Accurately weigh 3 mg of PTX into a 3 mL volumetric flask and dilute to the mark with methanol to prepare a stock solution with a concentration of 1 mg / mL. Subsequently, the stock solution was serially diluted to obtain PTX standard solutions with concentrations of 50, 25, 10, 5, 3, 1, and 0.5 μg / mL. The solutions were analyzed under chromatographic conditions, and a standard curve of PTX content was plotted with peak area on the ordinate and concentration on the abscissa.

[0111] The results are as follows Figure 19 As shown, the standard equation for PTX is y = 18408x - 5185.4, and the linear correlation coefficient R0 is... 2 The value of 0.9999 indicates that there is a good linear relationship between the solution concentration of PTX and the absorption peak area in the concentration range of 0.5-50 μg / mL.

[0112] Determination of the lowest limit of quantitation (LLOQ) The lowest concentration of the standard curve, i.e., 0.5 μg / mL, was selected as the lower limit of quantitation. Six samples were prepared in parallel and injected and measured according to the chromatographic conditions. The concentration of PTX was calculated based on the standard curve.

[0113] The results of the analysis of the lower limit of quantitation are shown in Table 2.

[0114]

[0115] The results showed that the accuracy of PTX was 100% and the RSD value was 1.03%, which met the measurement requirements.

[0116] Precision and accuracy determination Precisely prepare low, medium, and high concentrations of PTX, namely 1 μg / mL, 5 μg / mL, and 25 μg / mL, respectively. Prepare five replicates for each concentration and analyze them under the chromatographic conditions described above. Calculate intra-day precision and accuracy based on the standard curve. Perform continuous injections for three days and calculate inter-day precision and accuracy based on the standard curve.

[0117] The results of the precision and accuracy analysis are shown in Table 3.

[0118]

[0119] The results showed that the intra-batch precision of the low, medium, and high concentration samples were 0.84%, 0.53%, and 0.43%, respectively, and the intra-batch accuracy was 99.18%, 99.75%, and 100.06%, respectively. After three consecutive days of injection, the inter-batch precision of the low, medium, and high concentration samples were 1.32%, 1.11%, and 1.13%, respectively, and the inter-batch accuracy was 100.11%, 100.49%, and 100.70%, respectively. All results met the measurement requirements.

[0120] Establishment of the DOX Standard Curve Accurately weigh 2 mg of DOX into a 2 mL volumetric flask, and dilute to the mark with pure water to prepare a stock solution with a concentration of 1 mg / mL. Subsequently, the stock solution was gradually diluted to obtain DOX standard solutions with concentrations of 5, 3, 1, 0.5, 0.25, and 0.05 μg / mL. Fluorescence intensity was measured using a fluorescence spectrometer: detection wavelengths were Ex 480 nm and Em 500-700 nm. A standard curve of DOX content was plotted with fluorescence intensity (F) as the ordinate and concentration (C) as the abscissa.

[0121] The results are as follows Figure 20 As shown, the standard equation for DOX is y = 108.44x + 6.4442, and the linear correlation coefficient R² is 0.9998, indicating that there is a good linear relationship between the solution concentration of DOX and the fluorescence intensity in the concentration range of 0.05-5 μg / mL.

[0122] Determination of drug loading and encapsulation efficiency of drug-loaded microspheres Accurately weigh 5 mg of each drug-loaded microsphere, place them in centrifuge tubes, and crush them. Add 6 mL of methanol to the PTX-loaded microspheres and 6 mL of HCl solution (pH=3) to the DOX-loaded microspheres. Sonicate the centrifuge tubes for 30 min, then centrifuge at 4000 rpm for 10 min. Collect the supernatant and filter it through a 0.22 μm filter membrane. Analyze the supernatant from the PTX-loaded microspheres under the above chromatographic conditions, and calculate the PTX content in the sample based on the PTX standard curve. For the DOX-loaded microspheres, measure the fluorescence intensity of the supernatant using a fluorescence spectrometer, and calculate the DOX content loaded in the microspheres based on the DOX standard curve. Calculate the drug loading (DL%) and encapsulation efficiency (EE%) of the microspheres using the following formulas.

[0123] ; .

[0124] Where W1 and W2 represent the weight of the drug in the microsphere and the weight of the entire microsphere, respectively, and W3 represents the weight of the drug in the rinsing solution. All results are expressed as mean ± standard deviation (n=3).

[0125] The results showed that the drug loading of PTX@HA Mps was 3.14±0.14%, and the encapsulation efficiency was 50.74±4.73%. The drug loading and encapsulation efficiency of DOX@CA-HA Mps, prepared under the same optimal drug loading conditions, were determined using fluorescence spectroscopy. The results showed that the drug loading of DOX@CA-HA Mps was 3.12±0.28%, and the encapsulation efficiency was 80.65±3.47%. Since the theoretical density of hydroxyapatite (3.15 g / cm³) is approximately three times that of commonly used polymer carrier materials (such as PLGA), the actual drug loading of the two types of drug-loaded microspheres was approximately three times that of the polymer microspheres, indicating that the drug-loaded sustained-release microspheres prepared by this method have high drug loading and good encapsulation efficiency.

[0126] Example 4 In vitro release study of drug-loaded microspheres In vitro release curve determination of drug-loaded microspheres The in vitro release behavior of drug-loaded microspheres was investigated using the dialysis bag method. This method eliminates the need to separate the formulation from the release medium and effectively reduces measurement bias caused by sample loss during long-term testing, ensuring accurate results. Currently, the dialysis bag method has gradually become an important tool for studying the in vitro release behavior of micro / nano formulations. Accurately weighed drug-loaded microspheres were placed into pre-treated dialysis bags (MW=14000Da). The release medium was phosphate-buffered saline (PBS) at pH 7.4. Due to the poor solubility of PTX in PBS, 2% sodium dodecyl sulfate (SDS) was added as a co-solvent. The dialysis bags were placed in a constant-temperature shaking incubator at 37℃ and a shaking speed of 100 rpm. At regular intervals, 1 mL of release medium was removed, and the same volume of fresh release medium was added. All extracted samples were filtered through a 0.22 μm aqueous filter. Finally, PTX samples were quantitatively determined using the above chromatographic conditions, and DOX samples were quantitatively determined using fluorescence spectroscopy. All measurements were made in triplicate, and the results were expressed as mean ± standard deviation (n=3).

[0127] The results are as follows Figures 21-23 As shown, Figure 21 The figure shows the in vitro release curve of PTX from hydroxyapatite microspheres prepared under optimal drug loading conditions. As can be seen from the figure, PTX can be continuously released from HA microspheres in vitro for up to 41 days. The release behavior can be divided into two phases: the first phase is from 0 to 8 days, during which the drug release rate is relatively fast, with a cumulative PTX release rate of 28.84%; the second phase is from 8 to 44 days, during which the release rate slows down and gradually stabilizes, with a cumulative PTX release rate of 44.28% at 44 days.

[0128] Figure 22 and Figure 23This is the in vitro release curve of DOX from citric acid-modified hydroxyapatite microspheres prepared under optimal drug loading conditions. Figure 22 It is known that PTX can be continuously released in vitro from HA microspheres for up to 46 days. The release behavior can be divided into two phases: the first phase is from 0 to 10 days, during which the drug release rate is relatively fast, with a cumulative DOX release rate of 20.44%; the second phase is from 10 to 46 days, during which the release rate slows down, but the cumulative release rate continues to increase, reaching 37.45% DOX accumulation at 46 days. Compared to existing technologies, this invention has a moderate drug loading capacity and achieves continuous drug release for up to 46 days, making it highly promising for scenarios requiring long-term, stable drug delivery.

[0129] Study on the in vitro release mechanism of drug-loaded microspheres To investigate the in vitro drug release behavior of drug-loaded microspheres, the in vitro release data of the microspheres were fitted with zero-order kinetic models, first-order kinetic models, Higucci models, Cosmayer-Pepper models, and Weibull models, respectively.

[0130] Q = A + K × T; Q = A * (1 – exp(–K × T)); Q = A + K × T 1 / 2 ; Q = A + K × T n ; Q = K – (K – A) × exp(– (B × T) C ).

[0131] Where Q is the cumulative amount of drug released within time T, A, B, and C are constants, K is the kinetic constant, and n is the diffusion constant.

[0132] The relevant parameters and fitting results obtained by linear regression for each dynamic model are shown in Tables 4 and 5.

[0133]

[0134]

[0135] The results in the table show that, for the PTX@HA Mps system, the correlation coefficient R of the Weibull model is... 2has the highest value and provides the best fitting effect for the in vitro release data of PTX. The release exponent n is 0.7258, which is slightly lower than 0.75, indicating that the release process of PTX is mainly dominated by Fick diffusion. The migration of drug molecules from the surface and internal pores of microspheres into the release medium is mainly affected by the length of diffusion path and pore tortuosity, and no obvious behaviors such as framework erosion or carrier swelling occur. From the perspective of the release process itself, the drug release rate is relatively fast in the early release stage, because PTX molecules account for a relatively large proportion in the pores on the surface and shallow layer of the microspheres. The diffusion path of this part of the drug is relatively short, and its binding to the carrier is also relatively weak. Under a certain concentration gradient, it is easier to dissolve and diffuse rapidly into the release medium; as the release time gradually prolongs, the drug begins to enter a relatively slow release stage, and the cumulative release curve gradually tends to a plateau, which indicates that PTX molecules distributed in the deep pores inside the microspheres play a major role at this time. The diffusion path of this part of the drug in the pores is more tortuous, and at the same time, it is limited by the pore size, so the diffusion resistance increases significantly, which prolongs the overall release process, and finally shows a typical long-acting sustained-release characteristic The results in Table 5 show that the Korsmeyer-Peppas model has a correlation coefficient R for the in vitro release data of DOX@HA Mps 2 is the highest and the fitting effect is the best. Its n value is 0.564, indicating that the drug release belongs to non-Fick diffusion kinetics (0.43 < n < 0.85), that is, the release of DOX is jointly regulated by the dual mechanisms of drug diffusion and dissociation of electrostatic interaction. DOX releases rapidly in the initial release stage (0~10 days), which is mainly attributed to the fact that the electrostatic interaction between the drug molecules adsorbed on the microsphere surface and in the near-surface pores and the carboxyl groups (-COO - ) on the microsphere surface is relatively weak, and the diffusion path is short, so the drug rapidly desorbs and diffuses into the release medium under the concentration gradient. Compared with the hydrophobic drug PTX, the initial release rate of DOX is gentler, which benefits from the strong electrostatic adsorption between the carboxyl groups introduced by citric acid modification and the protonated amino groups (-NH3 + ) in DOX molecules, which effectively inhibits the burst release of the drug. As the release time prolongs (10~46 days), it enters the slow release stage. This stage corresponds to the desorption and diffusion process of DOX molecules loaded in the deep pores inside the microspheres. Due to the strong electrostatic interaction and hydrogen bonding between DOX and the carboxyl groups on the surface of CA-HA, drug molecules need to overcome high binding energy to dissociate from the adsorption sites, so the release rate is significantly reduced. Meanwhile, the tortuous path of the internal pores of the microspheres further prolongs the diffusion time of the drug, and the synergistic effect of the two achieves the long-acting sustained-release effect.

[0136] Comparative Example 1 Based on Example 2, porous hydroxyapatite microspheres (HA Mps) prepared in Example 1 were used to replace CA-HAMps for drug loading under optimal drug loading conditions. The drug loading and encapsulation efficiency were calculated and compared with those of Example 2. The results are as follows: Figure 24 As shown.

[0137] The results showed that the highest drug loading and encapsulation efficiency of unmodified microspheres loaded with DOX was 0.4±0.07% and 25.68±1.64%, respectively; while the highest drug loading and encapsulation efficiency of citric acid modified microspheres loaded with DOX was 3.09±0.33% and 79.94±2.49%, respectively. The drug loading and encapsulation efficiency of unmodified microspheres adsorbing doxorubicin hydrochloride were significantly lower than those of the citric acid modified microspheres in Example 2.

[0138] Comparative Example 2 Referring to existing technology (Yang Hui. Biomimetic Construction of Micro / Nano Hierarchical Hydroxyapatite and Its Influence on Mesenchymal Stem Cell Behavior [D]. Doctoral Dissertation, South China University of Technology, 2014), citric acid hierarchical hydroxyapatite microspheres were prepared by hydrothermal method. The specific steps are as follows: First, dissolve diammonium hydrogen phosphate ((NH4)2HPO4) in deionized water, and adjust the pH of the solution to 5.8-6.0 with nitric acid. Then add calcium nitrate (Ca(NO3)2) to increase the Ca2+ concentration in the solution. 2+ / PO4 3- The molar ratio was maintained at 1.6–1.7. The pH of the solution was adjusted to 5.0 using nitric acid. Sodium citrate (CtNa3) was added to the above mixture to a concentration of 20 mg / mL, and the mixture was stirred until completely dissolved to obtain the precursor mixture.

[0139] The above precursor mixture was transferred to a high-pressure reactor, with the mixture occupying 50%–80% of the total reactor volume. The reactor was placed in an oven and reacted at 220°C for 10 hours. After the reaction, it was allowed to cool naturally to room temperature. The reaction product was washed repeatedly with deionized water 3–5 times to remove residual sodium citrate and unreacted inorganic salt ions. The washed product was dried in a constant-temperature drying oven to obtain hollow hierarchical hydroxyapatite microspheres.

[0140] The hollow hierarchical hydroxyapatite microspheres prepared by this method have a surface composed of HA nanorods with an average particle size of approximately 2.8 μm, a wall thickness of approximately 428 nm, a cavity length of approximately 2.5 μm, a width of approximately 1.6 μm, and a pore size distribution between 1.7 and 9.69 nm. The specific surface area is as high as 225 m² / g. 2 / g.

[0141] Based on Example 2, hollow hierarchical hydroxyapatite microspheres prepared in Comparative Example 2 were used to replace CA-HAMps for drug loading under optimal drug loading conditions, and the drug loading amount and encapsulation efficiency were calculated.

[0142] The results showed that its DOX loading was only 0.5%, and the encapsulation efficiency was 21.51%, significantly lower than that of CA-HAMps in Example 2 (drug loading 3.12%, encapsulation efficiency 80.65%). The reason for this is that although the microspheres in Comparative Example 2 had a higher specific surface area, theoretically providing more drug adsorption sites, their pore size distribution was 1.7–9.69 nm, falling within the microporous to mesoporous range. While DOX molecules (molecular weight approximately 580 Da, kinetic diameter approximately 0.8–1.0 nm) could enter the pores, the smaller pore size limited the diffusion and efficient filling of drug molecules. Furthermore, the surface of these HA microspheres was not modified with citric acid grafting. Citric acid was used as a template agent to regulate crystal growth during synthesis, rather than as a surface modifier. The lack of abundant carboxyl functional groups on the surface prevented the provision of strong electrostatic binding sites for positively charged DOX. Therefore, its drug loading and encapsulation efficiency were significantly reduced.

[0143] Comparative Example 3 Based on Comparative Example 2, the concentration of sodium citrate (CtNa3) was adjusted to 0.3 mol / L (precursor mixture system). Other steps were the same as in Comparative Example 2. The results showed that the hydrothermal reaction could not proceed normally, and the target hollow hierarchical hydroxyapatite microspheres could not be synthesized; no well-crystallized hydroxyapatite product was obtained.

[0144] Comparative Example 4 First, APTES amylation modification was performed, followed by reaction with sodium carboxymethyl cellulose (CMC) to obtain sodium carboxymethyl cellulose modified porous hydroxyapatite microspheres. The steps are as follows: Amination modification: APTES was added to 80% anhydrous ethanol to make the concentration 20 mmol / L, and the mixture was stirred at room temperature for 30 min for hydrolysis. A certain amount of hydroxyapatite microspheres were added, and the mixture was shaken at room temperature for 24 h. After centrifugation, the microspheres were washed with ethanol and water alternately and dried at 60 °C to obtain amination-modified hydroxyapatite microspheres.

[0145] Carboxylation modification: First, an NHS-CMC intermediate was prepared, and CMC was activated under neutral and acidic conditions. CMC was dissolved in neutral phosphate buffer (PBS, pH=7.2) to prepare a 2 mg / mL solution; EDC and NHS were dissolved in PBS buffer to prepare 5 mg / mL EDC and NHS solutions, respectively. 680 μL of CMC solution, 120 μL of EDC solution, and 200 μL of NHS solution were added to 2 mL centrifuge tubes, respectively, to make the concentrations of EDC and NHS 0.6 and 1 mg / mL, and hydrolyzed at room temperature for 30 min. Aminated hydroxyapatite microspheres were added, and the mixture was shaken at room temperature for 24 h to allow for complete reaction. The mixture was then filtered and dried to obtain sodium carboxymethyl cellulose modified microspheres.

[0146] Based on Example 2, sodium carboxymethyl cellulose modified microspheres prepared in Comparative Example 4 were used to replace CA-HAMps, and drug loading was performed according to the optimal drug loading process conditions. The results are as follows. Figure 25 As shown.

[0147] The results showed that the sodium carboxymethyl cellulose modified microspheres prepared in Comparative Example 4 had the highest drug loading and encapsulation efficiency of 1.01±0.06% and 56.9±1.33%, respectively; while the citric acid modified microspheres in Example 2 had the highest drug loading and encapsulation efficiency of 3.09±0.33% and 79.94±2.49%, respectively. This indicates that the drug loading and encapsulation efficiency of the sodium carboxymethyl cellulose modified microspheres prepared in Comparative Example 4 were significantly lower than those of the citric acid modified microspheres in Example 2.

[0148] Comparative Example 5 Based on Example 1, folic acid-modified HA Mps were synthesized by replacing citric acid with the same molar mass of folic acid. Then, drug loading was performed according to the optimal drug loading conditions of Example 2.

[0149] The results showed that its DOX drug loading was only 1.84%, and the encapsulation efficiency was 45.12%. Simultaneously, its sustained-release period was shortened to less than 30 days. Although folic acid contains three carboxyl groups and can be grafted with HA through coordination mechanisms, its molecular size is much larger than that of citric acid. After grafting, the effective density of surface carboxyl groups is reduced, and some mesoporous channels are blocked, leading to a decrease in the electrostatic adsorption efficiency of DOX, a significant reduction in encapsulation efficiency and drug loading, and a corresponding weakening of sustained-release performance. This data proves that not all carboxyl group modifiers can achieve the same effect as citric acid; the matching degree between molecular size, grafting density, and pore structure is the key variable determining drug loading performance.

[0150] Comparative Example 6 The composite modified microspheres were prepared according to existing technology (Jiang Liuyun et al. A modification method and application of hydroxyapatite [P]. CN103387756A, 2013.), and the steps are as follows: The porous hydroxyapatite microspheres (HA Mps) prepared in Example 1 were dispersed in 100 ml of N,N-dimethylformamide, and then 0.5 g of citric acid was added. The mixture was heated and stirred at 120 °C for 6 hours. After filtration, washing, and drying, the microspheres were ultrasonically dispersed in 100 ml of xylene for 20 minutes at a power of 200 W, and then heated to 100 °C. 2.5 g of D,L-lactide was dissolved in 25 ml of xylene under N2 protection at 120 °C, and then added to the xylene dispersion of the nano-hydroxyapatite. 0.0025 g of stannous octoate catalyst was added, and the mixture was heated and stirred at 120 °C under N2 protection for another 6 hours. After the reaction was complete and cooled to room temperature, the microspheres were filtered, washed with dichloromethane, and dried to obtain the composite-modified microspheres.

[0151] Based on Example 2, the composite modified microspheres prepared in Comparative Example 4 were used to replace CA-HA Mps for drug loading under optimal drug loading conditions. The results showed that the DOX loading of the composite modified microspheres was less than 1.0% and the encapsulation efficiency was less than 30%, which was far inferior to CA-HA Mps in Example 2.

[0152] Comparative Example 6 demonstrates that even when HA is treated with citric acid, the carboxyl groups introduced by the citric acid treatment act as initiation sites in the subsequent lactide grafting reaction, participating in ring-opening polymerization. The carboxyl groups are then completely consumed, and PLA chains cover the HA surface and the inner walls of the pores. Ultimately, the surface of the microspheres is primarily exposed with hydrophobic PLA molecular chains, exhibiting a weakly negative or near-neutral surface charge and lacking free -COO groups. - PLA cannot effectively electrostatically adsorb positively charged DOX. At the same time, the PLA graft layer will block some of the entrances to the mesoporous channels, making it difficult for DOX molecules to enter the depth of the channels, and the hydrophobic surface of PLA is also not conducive to the adsorption and wetting of hydrophilic DOX.

[0153] Example 5 Based on Example 1, the amount of citric acid was adjusted to 0.03 mol / L, 0.5 mol / L, and 3.0 mol / L, respectively, to obtain different citric acid-modified porous hydroxyapatite microspheres.

[0154] Drug loading was performed according to the optimal drug loading conditions in Example 2. The results showed that the DOX encapsulation efficiency of porous hydroxyapatite microspheres modified with 0.03 mol / L citric acid was only 40.12%, the DOX encapsulation efficiency of porous hydroxyapatite microspheres modified with 0.5 mol / L citric acid was 85.58%, and the DOX encapsulation efficiency of porous hydroxyapatite microspheres modified with 3.0 mol / L citric acid was 31.84%. This indicates that insufficient citric acid resulted in only a small number of citric acid molecules grafted onto the microsphere surface, insufficient carboxyl group coverage density, and an inability to provide sufficient COO2. - Site and NH3 of DOX+ Highly efficient electrostatic binding occurs. With excess citric acid, multilayer adsorption occurs on the HA surface, but the outer layer of citric acid adheres only through physical action and is easily detached during washing. Simultaneously, free citric acid in the solution forms soluble complexes with calcium ions on the HA surface, corroding the microsphere surface and disrupting the pore structure. Excessive ionic interactions can also lead to re-agglomeration, resulting in a decrease in DOX encapsulation efficiency. A better drug loading effect can be achieved within the range of 0.3–0.5 mol / L.

[0155] This invention presents a method for preparing porous hydroxyapatite microspheres based on a combined electrostatic spraying and high-temperature sintering process, successfully constructing a drug delivery platform capable of simultaneously loading hydrophilic and hydrophobic drugs. The preparation of the microspheres, optimization of process parameters, and screening of sintering parameters were systematically studied. Surface functionalization modification and structural characterization were performed on the microspheres prepared under optimized conditions. Finally, the in vitro release of drug-loaded microspheres prepared under optimal drug loading conditions was evaluated. The finally prepared porous hydroxyapatite microspheres exhibited spherical morphology, uniform particle size, and controllable pore structure, demonstrating excellent drug loading performance and sustained-release capacity. Therefore, porous hydroxyapatite microspheres prepared based on electrostatic spraying-high-temperature sintering technology hold promise as a universal carrier platform for both hydrophilic and hydrophobic drugs.

[0156] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of this invention are still within the scope of protection of this invention.

Claims

1. A porous hydroxyapatite microsphere, characterized in that, The porous hydroxyapatite microspheres have citric acid grafted onto both their outer and inner surfaces, giving them a porous structure; the specific surface area of ​​the porous hydroxyapatite microspheres is 25-45 m². 2 / g, with an average pore size of 22-35nm; The method for preparing the porous hydroxyapatite microspheres includes the following steps: Hydroxyapatite microspheres and citric acid solution were mixed evenly and reacted by shaking at pH 5-8. The reaction product was washed and dried to obtain porous hydroxyapatite microspheres. The mass-to-volume ratio of hydroxyapatite microspheres to citric acid solution was (0.1-0.5) g: 4 mL; The preparation method of the hydroxyapatite microspheres includes the following steps: (a) Nano-hydroxyapatite and sodium alginate solution are mixed evenly to obtain a premixed solution; (b) The premixed solution was sprayed into the calcium chloride solution to prepare hydroxyapatite-calcium alginate composite microspheres; (c) The hydroxyapatite-calcium alginate composite microspheres are subjected to segmented high-temperature sintering to obtain the hydroxyapatite microspheres; In step (c), the segmented high-temperature sintering process is as follows: heat up to 90-120℃ at 3-10℃ / min and hold for 0.5-2h; then heat up to 320-350℃ at 3-10℃ / min and hold for 1-3h; then heat up to 580-620℃ at 3-10℃ / min and hold for 1-3h; finally, cool down to 150-250℃ at 3-10℃ / min and then cool. In step (a), the mass ratio of sodium alginate to nano-hydroxyapatite in the sodium alginate solution is (0.5-2):(1.5-6). In step (b), the concentration of the calcium chloride solution is 3-5 wt%.

2. The porous hydroxyapatite microspheres according to claim 1, characterized in that, The porous hydroxyapatite microspheres have a specific surface area of ​​26.55-40.89 m². 2 / g, with an average pore size of 23.38-30.36nm.

3. The method for preparing porous hydroxyapatite microspheres according to claim 1 or 2, characterized in that, Includes the following steps: Hydroxyapatite microspheres and citric acid solution were mixed evenly and reacted by shaking at pH 5-8. The reaction product was washed and dried to obtain porous hydroxyapatite microspheres. The mass-to-volume ratio of hydroxyapatite microspheres to citric acid solution was (0.1-0.5) g: 4 mL; The preparation method of the hydroxyapatite microspheres includes the following steps: (a) Nano-hydroxyapatite and sodium alginate solution are mixed evenly to obtain a premixed solution; (b) The premixed solution was sprayed into the calcium chloride solution to prepare hydroxyapatite-calcium alginate composite microspheres; (c) The hydroxyapatite-calcium alginate composite microspheres are subjected to segmented high-temperature sintering to obtain the hydroxyapatite microspheres; In step (c), the segmented high-temperature sintering process is as follows: heat up to 90-120℃ at 3-10℃ / min and hold for 0.5-2h; then heat up to 320-350℃ at 3-10℃ / min and hold for 1-3h; then heat up to 580-620℃ at 3-10℃ / min and hold for 1-3h; finally, cool down to 150-250℃ at 3-10℃ / min and then cool.

4. The preparation method according to claim 3, characterized in that, The concentration of the citric acid solution is 0.3-0.5 mol / L.

5. The use of the porous hydroxyapatite microspheres according to claim 1 or 2 in the preparation of a drug delivery carrier, wherein the drug comprises a cationic hydrophilic drug.

6. The application according to claim 5, characterized in that, The cationic hydrophilic drug is one or more of doxorubicin hydrochloride, daunorubicin, epirubicin, mitoxantrone, cisplatin, carboplatin, and oxaliplatin.

7. The application according to claim 5, characterized in that, The drug also includes a hydrophobic drug; the hydrophobic drug is one or more of paclitaxel, docetaxel and cabazitaxel.

Citation Information

Patent Citations

  • Hollow hierarchical hydroxyapatite microspheres and preparation method and application thereof

    CN103058159B

  • Modification method and application of hydroxyapatite

    CN103387756A

  • Method for preparing porous hydroxyapatite microspheres by using ultrasonic assisted multiple emulsion method

    CN106430138A

  • Preparation method of magnesium-doped hydroxyapatite drug-loaded microsphere

    CN110272032A

  • Polycaprolactone / nano-hydroxyapatite-citric acid composite material and patch absorbable memory elastic ring

    CN112206354A